2010
DOI: 10.1113/jphysiol.2010.188508
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged space flight-induced alterations in the structure and function of human skeletal muscle fibres

Abstract: The primary goal of this study was to determine the effects of prolonged space flight (∼180 days) on the structure and function of slow and fast fibres in human skeletal muscle. Biopsies were obtained from the gastrocnemius and soleus muscles of nine International Space Station crew members ∼45 days pre-and on landing day (R+0) post-flight. The main findings were that prolonged weightlessness produced substantial loss of fibre mass, force and power with the hierarchy of the effects being soleus type I > soleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
254
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(265 citation statements)
references
References 47 publications
9
254
1
1
Order By: Relevance
“…Therefore, fiber-type differences cannot explain the divergent responses to flight. Previous studies investigating the effects of exercise loading on human skeletal muscle during a prolonged (;180 days) exposure to space weightlessness have shown that mass loss in limb muscles is exponential with the duration of flight and that aerobic and low intensity resistance exercise countermeasures fail to adequately protect muscle mass, especially of the antigravity soleus muscle (33,34). The lack of mass loss in MA muscles revealed in this study could be a protective effect, at least for the short period of an ;13 days of space flight, by chewing-induced loading of these muscles, the specific physiological characteristics that masticatory muscles possess, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fiber-type differences cannot explain the divergent responses to flight. Previous studies investigating the effects of exercise loading on human skeletal muscle during a prolonged (;180 days) exposure to space weightlessness have shown that mass loss in limb muscles is exponential with the duration of flight and that aerobic and low intensity resistance exercise countermeasures fail to adequately protect muscle mass, especially of the antigravity soleus muscle (33,34). The lack of mass loss in MA muscles revealed in this study could be a protective effect, at least for the short period of an ;13 days of space flight, by chewing-induced loading of these muscles, the specific physiological characteristics that masticatory muscles possess, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…1). Through these experiments, the detrimental effects of microgravity on cellular function were consistently revealed, including inhibition of osteoblast differentiation [2,32,33], reduced osteoblast numbers [34], atrophy of skeletal muscle cells [14,35,36], impaired activation of immune cells and consequently the immune system [37 -39], abnormal formation of chondrocytes [40], and collapse of the cytoskeleton in T lymphoblastoid cells (Jurkat) [41], thereby displaying the impact of microgravity on various physiological systems.…”
Section: The Physiological Effects Of Spacefl Ight On Stem Cellsmentioning
confidence: 99%
“…IT IS WELL KNOWN that chronic muscle disuse in young healthy adults, as induced by spaceflight, bedrest, or immobilization, adversely affects muscle function. Although the loss of skeletal muscle mass induced by the disuse is widely acknowledged to contribute to this impairment, it has become increasingly evident that contractile dysfunction is disproportionately greater than decrements in cross-sectional area (CSA), as indicated by a decrease of specific force, suggesting a significant role played by decreased muscle "quality" in the dysfunction (4,9,15,33,51). It has been recently reported that the reduction of muscle quality can be attributed to a complex interaction of many factors that can affect neuromuscular transmission (4,24,42), muscle architecture (8,9), muscle fiber phenotype (14,38), and contractile apparatus properties (20,21).…”
mentioning
confidence: 99%